2017
DOI: 10.1002/jib.443
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative analysis of Chinese Gu-Jing-Gong spirit for its quality control

Abstract: The rapid quantitative analysis of food systems may offer improved control of food quality. In this work, the quantitative analysis of Chinese liquor was investigated using ultraviolet (UV) spectroscopy and a similarity algorithm. The potential application of this approach was evaluated using Chinese liquors, including the same and different batches of Gu‐Jing‐Gong spirits. The effectiveness of the proposed quality control quantitative model has been demonstrated, and the method could be applied to control the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…† The results showed that the spectra of each brand sample show statistically explainable quality uctuations; the Raman spectral intensities of MS, AM and CZ were found to be located in the ranges 462.6-757.8, 397.4-682.2 and 482.5-739.8, respectively. 7,29 The experimental results suggested that the spectral data conformed to certain statistical rules. At the same time, analysis also revealed spectral intensity overlap among brands, and therefore spectral intensity analysis alone cannot achieve brand identication.…”
Section: Characterization Of Dairy Products Using Raman Spectroscopymentioning
confidence: 79%
“…† The results showed that the spectra of each brand sample show statistically explainable quality uctuations; the Raman spectral intensities of MS, AM and CZ were found to be located in the ranges 462.6-757.8, 397.4-682.2 and 482.5-739.8, respectively. 7,29 The experimental results suggested that the spectral data conformed to certain statistical rules. At the same time, analysis also revealed spectral intensity overlap among brands, and therefore spectral intensity analysis alone cannot achieve brand identication.…”
Section: Characterization Of Dairy Products Using Raman Spectroscopymentioning
confidence: 79%
“…erefore, the statistical control chart method can be employed to analyze the fats (1760 cm −1 ), carbohydrates (1458 cm −1 ), and proteins (1019 cm −1 ), respectively. e statistical control chart can be realized using the following individual and moving range chart formulae [29,30]. For the individual (a) control chart, the formula is as follows:…”
Section: Statistical Analysis Of Raman Spectral Peak Intensity Ofmentioning
confidence: 99%
“…The average spectrum of all the collected Raman spectra of DX dairy products was taken as the theoretical true value of the sample, and then the Euclidean distances between each experimental sample and the theoretical true value were calculated. Next, an individual and moving range quality fluctuation control chart for DX dairy products was constructed using the calculated Euclidean distances, which can evaluate the quality stability of the samples (Zhang et al, 2017b), as shown in Supplemental Figure S1 Figure S1 reflected a high stability among DX dairy products when the full spectra were applied as the feature inputs. The Euclidean distances (average value) among the PZ, XY (the other famous dairy brands in China; used as control), and DX (experimental group) dairy products were calculated, as shown in Supplemental Figure S2 (https: / / doi .org/ 10 .3168/ jds .2018 -14569).…”
Section: Feature Extraction and Analysis Of Dairy Products Based On Rmentioning
confidence: 99%